Handbook of Vibrational Spectroscopy 2001
DOI: 10.1002/0470027320.s8962
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Vibrational Spectroscopy to the Analysis of Polysaccharide and Hydrocolloid Ingredients

Abstract: The applications of vibrational spectroscopy to study the structure of polysaccharide and hydrocolloid ingredients are presented. Vibrational spectroscopy, including infrared (IR) and Raman spectroscopies, has been used for both qualitative and quantitative analysis of starches and other polysaccharide ingredients. Some structural characteristics of starch and nonstarch polysaccharides have been studied using various vibrational spectroscopic techniques. The degree of substitution (DS) in modified polysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…The same percentage was achieved for the separation of hemp oil from the rest of the samples; this time the discrimination signals are 1775 and 1780 cm −1 , which could be attributed to the C=O vibrations from the amino acid residue found in the hempseeds and, also as minor constituents, in oil [19,20].…”
Section: Edible Oils Classification Based On Raman Spectroscopysupporting
confidence: 55%
See 1 more Smart Citation
“…The same percentage was achieved for the separation of hemp oil from the rest of the samples; this time the discrimination signals are 1775 and 1780 cm −1 , which could be attributed to the C=O vibrations from the amino acid residue found in the hempseeds and, also as minor constituents, in oil [19,20].…”
Section: Edible Oils Classification Based On Raman Spectroscopysupporting
confidence: 55%
“…Figure 3 presents the representative Raman spectra for the six types of the investigated oils and the markers which allowed their classification; these signals are: 1443, 1523, 1649, 1666, and 1780 cm −1 . The bands observed for the simultaneous classification can be tentatively assigned as follows: 1443 cm −1 to the CH deformation (CH 2 group) from the saturated part of oils [15], 1523 cm −1 to the C=C stretching vibration from carotenoids [16], 1649 and 1666 cm −1 to the C=C stretching vibration from cis conjugated systems and trans-CH=CHgroups [17,18], while 1780 cm −1 could be assigned to the C=O stretching vibration from some minor constituents-e.g., aspartic/glutamic acid residue [19] that exist in significant amounts in the appropriate seeds (e.g., hempseeds) [20]. Considering these data, we observed that the oils discrimination is mainly based on the peaks associated to the saturated part, to cis or trans configurations, to a characteristic band from carotenoids, or to a specific band (C=O) from different minor ingredients found in some oils.…”
Section: Edible Oils Classification Based On Raman Spectroscopymentioning
confidence: 80%
“…Previous literature reports on carbohydrates confirm the ability of Raman spectroscopy to distinguish different chemicals. Raman spectroscopy was shown to be a valuable tool for the studies of carbohydrates . For example, distinct Raman spectra were measured for 13 different sugars including glucose, fructose, starch and cellulose .…”
Section: Comparison Of the Portable And Lab‐based Raman Instrumentsmentioning
confidence: 99%